(untitled) (Defense and Security Studies, 2023)
The bulletproof vest material that is often used is a composite material. Composites are a mixture of two or more material elements, with different mechanical properties, which aim to obtain new materials that have better mechanical properties than the constituent materials. One alternative mixture of materials in composite materials is to use natural fibers as a substitute for kevlar fibers. In Indonesia, which has a tropical climate, natural fibers are very easy to obtain from various kinds of plants found in Indonesia. Along with the many plants obtained, a lot of waste is also produced because of this. So research was conducted on the utilization of the potential of natural fibers for alternative composites. With the experimental method, from the results of the experiment, the results obtained from the five natural fibers that have been discussed, namely pineapple leaf fiber, water hyacinth fiber, bark fiber, hemp fiber, and bamboo fiber, only pineapple leaf fiber has not met the National Institute of Justice (NIJ) standard, while the other four natural fibers have met the NIJ standard for bulletproof vests.